The process of acknowledging the autonomy of the laws of Ecclesial Communities in the canonical legal order - GIERŻON, GINTER (Prawo Kanoniczne, 2014)
The analysis of the Catholic discipline and doctrine shows that the acceptance of the capability of ecclesial communities to create their own legal systems was a long-term process. The Second Vatican Council and post-council canons were of crucial influence on the present legal order and the solution of the problem. The author proved that the evolution of the approach of the Church to the question formulated in the title of the article was expressed in the regulations included in can. 780 § 2, n. 1 CCCIC and art. 2 § 2, n. 1 DC, in which the autonomy of the laws of ecclesial communities was clearly acknowledged.